Demand for maize hybrids, seed subsidies, and seed decisionmakers in Zambia - Smale, Melinda; Mason, Nicole (International Food Policy Research Institute, 2012)
This analysis explores the determinants of demand for first-generation (F1) hybrid maize seed in Zambia based on a survey of maize growers during the 2010/11 cropping season. We estimate the determinants of demand with a control function approach to handle the potential endogeneity of the binary variable measuring subsidy receipt and compare determinants of demand between female and male seed decisionmakers. We find that hybrid seed use in Zambia is still very much an “affair of state” in that farmers’ use of F1 hybrids is explained largely by inclusion in FISP.